RESTLESS LEG SYNDROME AS A REASON OF CHRONIC INSOMNIA - Jakub Jędrychowski; Natalia Pacocha; Natalia Karpowicz; Julia Kaszucka; Justyna Popczyńska; Agnieszka Raczyńska; Małgorzata Krzyżanowska; Marta Zgierska; Kinga Kosiec; Oliwia Krzemień (International Journal of Innovative Technologies in Social Science, 2024)
Restless legs syndrome (RLS) is characterized by discomfort in the lower limbs with a strong need to move to bring relief. Based on the available literature and numerous studies on patient groups, we decided to summaries the aetiologias, risk factors, epidemiologies, and treatments for RLS. It is one of the most common causes of insomnia in both adult and child populations. Particularly at risk of developing RLS are people suffering from chronic renal failure, and pregnant women. Causes of RSL include mainly iron deficiency, and disturbances in dopaminergic transmission. Diagnosis is made primarily on the basis of the presence of symptoms, their severity, and frequency. Treatment first recommends non-pharmacological methods in the form of warm baths, massages, relaxation exercises, and avoidance of triggers. At a later stage, patients with more intractable symptoms are treated with oral iron supplementation, dopaminergic agonists, and alpha-2-delta ligands.